2021
DOI: 10.1007/s11356-021-18032-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3R4F cigarette smoke and IQOS heated tobacco product aerosol emissions

Abstract: In this study, the smoke from a 3R4F research cigarette and the aerosol generated by the Heated Tobacco Product IQOS, also referred to as the Tobacco Heating System (THS) 2.2 in the literature, were compared. The objective was to characterize the gas and suspended particulate matter compositions in the mainstream smoke from a combusted 3R4F cigarette and in the aerosol generated by IQOS during use. The results indicated that the determined aerosol emissions from IQOS were notably lower than in the cigarette sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
4
7
0
Order By: Relevance
“…These ultrafine, non-evaporating particles are characteristic of combustion-generated aerosols but are practically undetectable in IQOS aerosols. A similar characterization of TPM was found by Amoroz-Perez et al [ 41 ] and Kärkelä et al [ 42 ] using different experimental techniques, with aerosol and smoke from IQOS and 3R4C trapped in liquid media and analyzed by various techniques, including UV spectroscopy, GC-MS, and transmission electron microscopy. Pacitto et al [ 43 ], in an independent study, also found IQOS aerosol particles to be predominantly volatile liquid droplets by estimating their volatile fraction from the change in the surface-to-volume ratio of (assumed) spherical droplets whose main diameters showed a mean 10-factor decrease when passing from 30 °C to 300 °C.…”
Section: Theoretical Backgroundsupporting
confidence: 74%
See 1 more Smart Citation
“…These ultrafine, non-evaporating particles are characteristic of combustion-generated aerosols but are practically undetectable in IQOS aerosols. A similar characterization of TPM was found by Amoroz-Perez et al [ 41 ] and Kärkelä et al [ 42 ] using different experimental techniques, with aerosol and smoke from IQOS and 3R4C trapped in liquid media and analyzed by various techniques, including UV spectroscopy, GC-MS, and transmission electron microscopy. Pacitto et al [ 43 ], in an independent study, also found IQOS aerosol particles to be predominantly volatile liquid droplets by estimating their volatile fraction from the change in the surface-to-volume ratio of (assumed) spherical droplets whose main diameters showed a mean 10-factor decrease when passing from 30 °C to 300 °C.…”
Section: Theoretical Backgroundsupporting
confidence: 74%
“…This paper is an attempt to update and expand the speculations of Auer et al [53]. Their claim that IQOS emissions fit the concept of smoke is based on four arguments: detection of solid ultrafine particles in the TPM, detection of the same HPHCs found in tobacco smoke (such as CO), the existence of pyrolysis and other processes that also occur in the generation of mainstream CC emissions (see Section 3.1), and the possibility that some spots in tobacco sticks might be heated above 350 • C. These arguments contain a kernel of truth but do not prove the authors' claims: while solid particles and CO might be present in IQOS emissions, its TPM is overwhelmingly made of volatile liquid droplets [40][41][42][43], and CO and other compounds are found at much lower levels than in tobacco smoke [45,46,57,61]. Pyrolysis and distillation occur in generating IQOS aerosol, but as endothermic processes are irrespective of the presence of oxygen, while in the formation of tobacco smoke, they are preceded by a highly energetic, oxidizing, and exothermic ignition (see Sections 3.2 and 3.3).…”
Section: Htp Aerosols Are Not "Smoke"mentioning
confidence: 93%
“…Particles were detected after heating sticks of 15 different flavors using 5 different devices. Though particles were detected at lower concentrations compared to the emission of conventional cigarettes (about 23.5–44.5% of the concentration of CCs) 27 , the concentration is non-negligible in comparison to that of background air. Raw data of the PM recorded values both for background air and for the five sticks of LIL regular, smoked according to the ISO regime, are presented in Supplementary file Figure 2.…”
Section: Discussionmentioning
confidence: 79%
“…This observation is supported by the majority of newly identified studies and reviews. Quantified levels of the HPHCs investigated were either substantially lower from HTPs than from cigarettes [34][35][36][37][38][39][40] or undetectable or unquantifiable for HTPs [41]. The observed reduction in HPHC yields for HTPs when compared to cigarettes remains even when experimental machine smoking of the products is conducted under a range of extreme conditions of temperature and humidity [36].…”
Section: Harmful and Potentially Harmful Constituents (Hphcs)mentioning
confidence: 99%